PENGARUH FDR DAN NPF TERHADAP PROFITABILITAS (ROA) BANK SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2018-2022) - Muhammad Kharazi (STISNU Aceh, 2022)
This study aims to determine the effect of Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on Return on Assets (ROA) in Islamic banking listed on the Indonesia Stock Exchange (2018-2022 Period). This study uses a descriptive quantitative method with multiple linear regression analysis. The results of the study show that the ratio of FDR and NPF simultaneously influences the ROA of Islamic banking. While the partial results, FDR has a negative and insignificant effect on ROA, for the NPF ratio it has a negative and significant effect on ROA